Dual-Indicator Micro-Electro-Mechanical System Monitoring Method for Rock Instability Early Warning - Chen Chen; Mowen Xie; Yan Du; Xiaoyong Zhang (Applied Sciences)
Traditional displacement monitoring struggles to provide early warnings for sudden rock collapses. This study proposes a Micro-Electro-Mechanical System (MEMS) sensor-based monitoring method using dual dynamic indicators. By analyzing sensor mechanisms through vibration dynamics theory and establishing theoretical models via moment equilibrium equations, we derived a quantitative correlation between natural frequency (NF) and safety factor, identifying a 4:3 scaling coefficient specific to toppling-type unstable rocks. An innovative stability criterion algorithm integrating NF and the root mean square velocity amplitude ratio (RMS-VAR) was developed, revealing that RMS-VAR detects stability degradation three times faster than tilt measurements. Laboratory tests confirmed MEMS sensors’ reliability in monitoring NF, amplitude ratio, and tilt angles, demonstrating that sensor deployment strategies and rock geometry jointly determine model accuracy. This quantitative approach offers a novel solution for monitoring sudden geological hazards, combining timeliness with cost-effectiveness.